The Role of Multimodal AI in Revolutionizing Healthcare: A Perspective - Kalpesh Chodvadiya (National Journal of Medical Research)
Advancements in artificial intelligence (AI) are transforming the healthcare landscape. Multimodal AI, a paradigm that integrates diverse data types, holds the potential to address inefficiencies in healthcare delivery. This perspective explores the current applications and future promise of multimodal AI, emphasizing the need for trust, explainability, and rigorous clinical validation. Highlighting parallels between the detective work of data collection in healthcare and the problem-solving nature of AI, this article advocates for integrating AI to enhance efficiency, equity, and personalized care while maintaining the art of medicine.